CEO Characteristics on Cash Holdings & Overinvestment: Evidence from Indonesian Firms - Bella Joy Winarta; Neneng Djuaeriah; Yosman Bustaman (Journal of Management Practices, Humanities and Social Sciences, 2018)
The purpose of this research is to analyze the influence of CEO characteristic towards firms' cash holdings and over-investment of free cash flow. CEO gender is identified as independent variable where cash holdings and over-investment of free cash flow are the dependent variables. Other CEO characteristic such as age, education, tenure, firm size, market-to-book ratio, leverage, cash flow, capex, networking capital, dividend, free cash flow, managerial and state ownership are the control variable. This research used multiple regression on panel data of a sample of 24 companies listed in index LQ45 for the period from 2013 to 2017 with 61 female CEOs and 59 male CEOs in the sample. The research finds a positive significant relationship between female CEOs, cash holdings and over-investment. The results also show that female CEOs are having a higher level of cash holdings and resulted in lower level of over-investment problems. Female CEO also can mitigate the agency problem in the firm. The UET theory is used to support the findings in which CEO characteristic can influence the company,s performance and financial decision. UET literature focuses on executive demographic to explain corporate investment decision while this paper extends the application of the UET in the area of accounting. This research can be useful for companies to provide opportunities to female to reach the executive levels so that the companies can increase the proportion of women in executive levels. It also encourages policy makers to make regulations that address gender issues in organizations.